Effects of molasses on the quality, aerobic stability, and ruminal degradation characteristics of mixed ensilage of seed-used zucchini peel residue and corn stalk - Tengyu Wang; Zuoxing Huang; Ning Zhang; Kashaf Kareem; Xinwen Sun; Cuiling Shang; Dengke Hua; Xinfeng Wang (Frontiers in Sustainable Food Systems)
BackgroundThe objective of this study was to determine the optimal level of molasses required for ensiling the seed-used zucchini peel residue and corn stalks mixtures, using a 2:1 ratio of seed-used zucchini peel residue to corn stalks. The experiment included a control group (CON, with no molasses added), a 1% molasses group (M1, 10 g kg−1 fresh matter), a 2% molasses group (M2, 20 g kg−1 fresh matter), and a 3% molasses group (M3, 30 g kg−1 fresh matter). After 60 days of fermentation, samples of the silage were collected and analyzed for their chemical composition, fermentation quality, aerobic stability, and ruminal degradation characteristics.ResultCompared to the CON group, the addition of molasses significantly decreased both the pH and the ratio of ammonia nitrogen to total nitrogen (NH3-N/TN) in the ensilage mixture of seed-used zucchini peel residue and corn stalks. In the molasses-treated groups, the pH values decreased by 0.08, 0.09, and 0.13, respectively, compared to the control group. The NH3-N/TN ratios decreased by 1.52, 1.86, and 2.24, respectively, compared to the control group. Additionally, the contents of neutral detergent fiber (NDF) and acid detergent fiber (ADF) in the silage with molasses were significantly lower than those in the CON group. However, the addition of molasses reduced the aerobic stability of the feed, with the 3% molasses-added group showing a significant decrease in aerobic stability. Furthermore, the addition of molasses significantly improved the ruminal degradation rates of the silage, with the M3 group showing ruminal degradation rates of dry matter (DM), crude protein (CP), and ADF at 65.49, 55.26, and 46.18%, respectively.ConclusionThe addition of molasses is beneficial for improving the quality of the ensilage mixture of seed-used zucchini peel residue and corn stalks, improving the nutritional components and increasing the ruminal degradation rate.